MODAL SPLIT IN THE ŽILINA TRANSPORT MODEL - Drličiak, Marek (Perner’s Contacts, 2016)
The transport modeling is established process for many transport project all over the world. The four step model (FSM) is the primary tool for forecasting demand and performance of a transportation system. The trip generation, trip distribution and modal split are three steps which are calculated step by step or jointly. The calculated origin-destination matrices are used in final step – assignment. The article deals with the modal split of transport model of Žilina. The mentioned transport model has been used for transport master plan. The modal split requests the large data database from solved area. The data were evaluated from mobility survey. The quality of modal split mostly depends on utility of defined transport systems in the transport model. The most serious problem of modal split is the filling of database and them correctly evaluation.